2020
DOI: 10.1038/s41378-020-00222-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-cleaning semiconductor heterojunction substrate: ultrasensitive detection and photocatalytic degradation of organic pollutants for environmental remediation

Abstract: Emerging technologies in the field of environmental remediation are becoming increasingly significant owing to the increasing demand for eliminating significant amounts of pollution in water, soil, and air. We designed and synthesized MoS2/Fe2O3 heterojunction nanocomposites (NCs) as multifunctional materials that are easily separated and reused. The trace detection performance of the prepared sample was examined using bisphenol A (BPA) as the probe molecule, with limits of detection as low as 10−9 M; this det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Au NPs decorated cicada wing [233] 10 [237] unspecified concentration of malachite green, 1 µM thiram water-ethanol solution visible light photocatalytic degradation rinse with deionized water for 5 s -visible light (1000 W xenon lamp, 400-800 nm) irradiation for 50 mins -rinse with deionized water for 5 sblow dry with nitrogen gas near-full removal of analyte; slight drop off in SERS activity after each regeneration cycle, maintained more than 70% SERS activity after 5 cycles using malachite green as analyte; maintained more than 83% SERS activity using thiram as analyte MoS 2 /Fe 2 O 3 heterojunction nanocomposite [248] [253] 1.00×10 -6 M rhodamine 6G superhydrophobicity sonicated in 30 mL of deionized water for 10 mins analyte fully removed; SERS activity decreased by 17.3% after 6 cycles Si wafer decorated with hierarchical Ag nanostructures on indium oxide nano-branches [254] 2.1×10 -5 M rhodamine 6G water solution superhydrophobicity sonicated in isopropyl-alcohol bath for 10 mins SERS activity fully maintained for 10 cycles MIP@Ag [266] 1×10 -5 M bisphenol A in acetonitrile solution intermolecular interaction treatment with methanol-acetic acid solution (details unspecified)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au NPs decorated cicada wing [233] 10 [237] unspecified concentration of malachite green, 1 µM thiram water-ethanol solution visible light photocatalytic degradation rinse with deionized water for 5 s -visible light (1000 W xenon lamp, 400-800 nm) irradiation for 50 mins -rinse with deionized water for 5 sblow dry with nitrogen gas near-full removal of analyte; slight drop off in SERS activity after each regeneration cycle, maintained more than 70% SERS activity after 5 cycles using malachite green as analyte; maintained more than 83% SERS activity using thiram as analyte MoS 2 /Fe 2 O 3 heterojunction nanocomposite [248] [253] 1.00×10 -6 M rhodamine 6G superhydrophobicity sonicated in 30 mL of deionized water for 10 mins analyte fully removed; SERS activity decreased by 17.3% after 6 cycles Si wafer decorated with hierarchical Ag nanostructures on indium oxide nano-branches [254] 2.1×10 -5 M rhodamine 6G water solution superhydrophobicity sonicated in isopropyl-alcohol bath for 10 mins SERS activity fully maintained for 10 cycles MIP@Ag [266] 1×10 -5 M bisphenol A in acetonitrile solution intermolecular interaction treatment with methanol-acetic acid solution (details unspecified)…”
Section: Discussionmentioning
confidence: 99%
“…246 Amongst these materials, enhancing substrates based on semiconductors, such as ZnO, TiO 2 , and MoS 2 , stand out particularly since they are not only potentially cheap and stable alternatives to Ag and Au but are also photocatalytically active which allows for the construction of reusable substrates. [247][248][249][250] For example, in a proof-of-concept demonstration, Liu, Gao, et al designed photocatalytically active ternary ZnO/ZnS/MoS 2 nanocomposites, as shown in Figure 17D, which could be used as reusable substrates for SERS. 251 The nanocomposites were synthesized through in-situ chemical growth using phosphomolybdic acid hydrate (PMo 12 )@zeolitic imidazolate frameworks-8 (ZIF-8) as the precursor.…”
Section: Photocatalytic Regenerationmentioning
confidence: 99%
“…Serious environmental pollution is due to population growth and rapid economic development. 1 The treatment of water pollution and the production of clean energy have become urgent needs to improve ecology. 2 Semiconductor-based photocatalysis is considered an effective method to degrade organic molecules in water and purify air.…”
Section: Introductionmentioning
confidence: 99%
“… 41 A heterogeneous structure is possible by incorporating MO semiconductors with other MOs, which leads to type II heterojunctions having photocatalytic behavior. 42 Containing a higher number of oxidative radicals, both ZnO and In 2 O 3 create charge carriers at their interface may facilitate their photocatalytic performance. Besides, at a higher temperature, due to the increased transparency of the composite coating, light waves pass through and diminish any pollutants through photocatalytic reaction and antisoiling properties.…”
Section: Resultsmentioning
confidence: 99%